DIGITAL PARTICIPATION AND HERITAGE DOCUMENTATION: AN INTERFACE FOR SURVEYING ATTRIBUTES AND VALUES OF ARCHITECTURAL RUINS IN LARANJEIRAS, SERGIPE, BRAZIL - P. Freitas; P. Galvão; D. Doria (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2023)
In the 21st century, participation is a key factor for ensure effectiveness of safeguarding culturally significant buildings. Integration of local communities in the process of architectural conservation is seen as complex task, but also an excellent strategy to avoid top-bottom processes – “made by experts” – that tend to fail more often. Recording heritage buildings often need some level of expertise but also tend to support biases, in which the “expert” operator might reproduce his perception away from the values acknowledged by the different communities that live and support the heritage itself. This paper presents a prototype of a digital interface designed to record the values’ perception of derelict buildings of Laranjeiras’ heritage site, an 18th century urban settlement classified since 1996 and valued as a Brazilian national heritage by its architecture and historical significance in the Cotinguiba river basin in the State of Sergipe. The project used as a case study the ancient “Cinema Iris”, a popular building in the main street (“calçadão”). The methodology adopted the following procedures: 1) Survey; 2) Pre-selection of material attributes; 3) Integration; 4) Data collection; 5) Evaluation. As a primary product, yet to be perfected, the creation and application of the digital interface gave attention to the need for an integrated survey database of Laranjeiras’ ruins as perceived by the local community. Turning them into a collection of balanced values, the interface proved to be a positive tool to support the development of further conservation actions (design, management, and monitoring) in the heritage site.